Выполните преобразование по данной формуле.

1) (х + 5)^2;

2) (a - 2)^2;

3) (5а - 2)^2;

4) (4х + у)^2;

5) (а^2 - 1)^2. 6) (2 + у)^2;

7) (6 - с)^2;

8) (2х + 9); 8) (7m - 3n)^2;

9) (b + c^3)^2.

Решите, пожалуйста, ребята!

1

Ответы и объяснения

Лучший Ответ!
2014-01-25T17:06:54+00:00
1) (x+5)^2 = x^2+10x+25;
2) (a-2)^2 = a^2-4a+4;
3) (5a-2)^2 = 25a^2-20a+4;
4) (4x+y)^2 = 16x^2+8xy+y^2;
5) (a^2-1)^2 = a^4-2a^2+1;
6) (2+y)^2 = 4+4y+y^2;
7) (6-c)^2 = 36-12c+c^2;
8) ?
9) (b+c^3)^2 = b^2+2bc^3+c^6.